Plasticity and Evolution of (+)-3-Carene Synthase and (−)-Sabinene Synthase Functions of a Sitka Spruce Monoterpene Synthase Gene Family Associated with Weevil Resistance - Roach, Christopher R. (American Society for Biochemistry and Molecular Biology, 2014)
The monoterpene (+)-3-carene is associated with resistance of Sitka spruce against white pine weevil, a major North American forest insect pest of pine and spruce. High and low levels of (+)-3-carene in, respectively, resistant and susceptible Sitka spruce genotypes are due to variation of (+)-3-carene synthase gene copy number, transcript and protein expression levels, enzyme product profiles, and enzyme catalytic efficiency. A family of multiproduct (+)-3-carene synthase-like genes of Sitka spruce include the three (+)-3-carene synthases, PsTPS-3car1, PsTPS-3car2, PsTPS-3car3, and the (−)-sabinene synthase PsTPS-sab. Of these, PsTPS-3car2 is responsible for the relatively higher levels of (+)-3-carene in weevil-resistant trees. Here, we identified features of the PsTPS-3car1, PsTPS-3car2, PsTPS-3car3, and PsTPS-sab proteins that determine different product profiles. A series of domain swap and site-directed mutations, supported by structural comparisons, identified the amino acid in position 596 as critical for product profiles dominated by (+)-3-carene in PsTPS-3car1, PsTPS-3car2, and PsTPS-3car3, or (−)-sabinene in PsTPS-sab. A leucine in this position promotes formation of (+)-3-carene, whereas phenylalanine promotes (−)-sabinene. Homology modeling predicts that position 596 directs product profiles through differential stabilization of the reaction intermediate. Kinetic analysis revealed position 596 also plays a role in catalytic efficiency. Mutations of position 596 with different side chain properties resulted in a series of enzymes with different product profiles, further highlighting the inherent plasticity and potential for evolution of alternative product profiles of these monoterpene synthases of conifer defense against insects.